Ponce de León Elizondo, Ana (1998). Tiempo libre y rendimiento académico. Logroño: Universidad de La Rioja - Esther Gargallo Ibort (Universidad de La Rioja, 2013)
Ponce de León Elizondo, Ana (1998). Tiempo libre y rendimiento académico. Logroño: Universidad de La Rioja.